(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-3-10-20 More than half-century collection of geographically and functionally diverse lexicographic material on the territory of the Russian Empire allowed V.I. Dahl to determine the peculiarity of the language situation and the main directions of the development of the Russian language in the relationship between the interaction of inter-dialect and foreign-language interactions, largely correlated with the achievements of modern linguistics. Particularly significant in this regard are the comments of V.I. Dahl on the formation and development of secondary dialects in the vast territory of the Orenburg province, where the post of assistant to the Orenburg military governor allowed him to directly observe the features of Orenburg dialects, which are formed in isolation from maternal dialects in direct contact with the dialects of more than twenty provinces of the Russian Empire and in the neighborhood with Turk and Finno-Ugric languages. At the same time, V.I. Dahl notes the specifics of Cossack dialects, due to the status of the Cossacks in the border territories, as well as gender and socially significant differences in the speech of Cossacks and Cossacks. Filigree linguistic observations of V.I. Dahl on the variety of Orenburg dialects at the stage of their formation and development have scientific significance not only in historical terms, but also to a certain extent correlate with the modern level of studying dialects of late settlement territories, including studies in the field of interference, contact and specificity of the permeability of Russian dialects. Keywords: V.I. Dahl, Orenburg region, territory of late settlement, language situation, secondary dialects, Orenburg Russian dialects, Cossack dialects